Right to Education and Employment: A Step Towards Empowering Transgender Community - Vats, Naresh Kumar; Purohit, Megha (Kathmandu School of Law Review, 2017)
The term Transgender is generally used to refer to those people who do not incarcerate themselves into the socially constructed gender norms i.e. male or female. Despite having international instruments and constitutionalprovisions on safeguarding the right to equality of all persons, still transgendered people face social stigma in every aspect of their lives. They face numerous overlapping challenges, specifically discrimination in education and employment. Even while looking at the Vedic period, there was less recognition to eunuchs but during the Mughal period, they were enjoying the position as guardians of harems. They were alsogiven the privilege of guarding the holy places which they lost during the British period. They continue to face harassment on many occasions besides bullying at school and workplace. Now, India is still struggling to pass a Bill on Rights of transgendered ensuring to bring them into the mainstream of society. The right to education and employment, which are enshrined as a human right in the International Covenant on Civil & Political Rights, applies to all people irrespective of their sexual orientationbut due to prevalent social stigma and people’s attitude, the transgender community is facing various challenges. Hence, the paper is an attempt to provide a comprehensive overview on rights of education and employment of transgendered members. The approach in the paper is analytical and descriptive involving qualitative methodology. The study engages the internal and external desk-based research limited to specific rights to education and employment to the third gendered people.